Ruud Koek : Identificerend Licht. - Dittrich, K.L.L.M.; Flierman, A.H.; Nieuwenhuijzen Kruseman, A.C.; Thehu, Kim; van Iterson, Ad (Maastricht : Universiteit Maastricht, 2001)
The photo book Identifying Light by Ruud Koek is now published on the occasion of 25 years of existence of the University of Maastricht. Photographer Ruud Koek presents the university and her inhabitants. He puts together about fifty images in his own typical way and welds them into a photo report which can be interpreted as a search for identity. The photo's really show a distance between photograph and subject. This distance enables Koek to create sort of an interspace, in which he as the photographer is not the only storyteller, but the imagery has its own story to tell.
Engels
Nederlands
boek
Keywords: Koek, Ruud